2014
DOI: 10.1192/s1749367600004240
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the mental health needs of a rapidly growing megacity: the new Lagos Mental Health Initiative

Abstract: The Lagos State Government of Nigeria recently launched its Mental Health Policy and Work Plan aimed at addressing the mental health needs of Lagos, one of the world's fastest-growing megacities, and its nearby communities. This paper discusses the contextual basis of this initiative, its components and the challenges faced so far. It argues that urban centres deserve attention in the current push towards investing in mental health services in low- and middle-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Likewise, different types of psychotropic medications must always be made available. 7,12,[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]…”
Section: The Expected Challenges In Integrating Mental Healthcare Services Into Primary Healthcare Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, different types of psychotropic medications must always be made available. 7,12,[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]…”
Section: The Expected Challenges In Integrating Mental Healthcare Services Into Primary Healthcare Servicesmentioning
confidence: 99%
“…10 The WHO-AIMS report on mental health aspects of Nigeria and other published documents from the Lagos State showed that mental healthcare services have been neglected in Nigeria. [11][12][13][14][15][16] Nonetheless, the Lagos State government took the initiative of launching its mental health policy. 15 However, for the policy to be effective, the state must be proactive by looking into the mental health needs of the 18 million residents of the state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nigeria is a developing country located in the western part of Africa, with a massive population of 180 million people. The available mental health personnel are scanty [5][6] . There were 0.028 mental health outpatient facilities per 100,000 population and less than 300 specialist psychiatrists [5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The available mental health personnel are scanty [5][6] . There were 0.028 mental health outpatient facilities per 100,000 population and less than 300 specialist psychiatrists [5][6] . Although, specialist mental health hospitals were observed to be few and are mostly located in capital cities isolated from the rural communities making professional psychiatric services inaccessible and far from those living in rural areas [5][6] .…”
Section: Introductionmentioning
confidence: 99%